Rehabilitation robotics after stroke: a bibliometric literature review. (4th May 2022) - Zuccon, Giacomo; Lenzo, Basilio; Bottin, Matteo; Rosati, Giulio
ABSTRACT: Introduction: Stroke is the leading cause of long-term disability in developed countries. Due to population aging, the number of people requiring rehabilitation after stroke is going to rise in the coming decades. Robot-mediated neurorehabilitation has the potential to improve clinical outcomes of rehabilitation treatments. A statistical analysis of the literature aims to focus on the main trend of this topic. Areas covered: A bibliometric survey on post-stroke robotic rehabilitation was performed through a database collection of scientific publications in the field of rehabilitation robotics. By covering the last 20 years, 17, 429 sources were collected. Relevant patterns and statistics concerning the main research areas were analyzed. Leading journals and conferences which publish and disseminate knowledge in the field were identified. A detailed nomenclature study was carried out. The time trends of the research field were captured. Opinions and predictions of future trends that are expected to shape the near future of the field were discussed. Expert opinion: Data analysis reveals the continuous expansion of the research field over the last two decades, which is expected to rise considerably in near future. More attention will be paid to the lower limbs rehabilitation and disease/design specific applications in early-stage patients.